ANALISIS POSTER VIDEO KLIP LATHI : KAJIAN SEMIOTIKA FERDINAND DE SAUSSURE - Sitompul, Anni Lamria; Patriansah2, Mukhsin; Pangestu, Risvi (Besaung : Jurnal Seni Desain dan Budaya)
Occasionally, communication continues to develop, ranging from the use of smoke signals, drums, paper inventions, telegraphs, telephones, computers, emails to the internet as a medium of communication. One of the communication media that is developing today is posters. Posters used to convey messages or information to the public are generally printed and placed in public area or through social media. The visual markings used by the designer in the poster are addressed to the public so that the public can understand the message and the purpose of the information. The use of poster visual marks from the video clip of the song "Lathi" which raises the theme of toxic relationships is very interesting to be traced, dissected and analyzed using a semiotic approach. Semiotics is the study of the science of the signs that exist in human life and the meaning behind the sign. The visual mark that will be raised for analysis in this paper is the sign system in the form of posters from the video clip of the song "Lathi" by Andy Andrians (Art Director of Lathi).